The Effect of Moving Ball and Stationary Ball Shooting Drills on Kick Accuracy in Soccer Among Eighth-Grade Students of SMP Negeri 18 Medan - S, Octavianus L.; Isnandar, Muhammad (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2025)
This research investigates the effectiveness of the Problem-Based Learning (PBL) model in improving the shooting skills of eighth-grade students in football at MTS Darul Ilmi during the 2022/2023 academic year. The study applied a Classroom Action Research (CAR) method conducted in two cycles involving 27 students. Each cycle included the stages of planning, implementation, observation, and reflection. Data collection was carried out through lesson plans, observation sheets, and documentation, and analyzed using percentage-based descriptive statistics. The findings revealed a significant improvement in students’ shooting performance: the average score increased from 75 in cycle I (59.26% mastery) to 86 in cycle II (88.89% mastery), surpassing the minimum learning target of 75%. Moreover, students showed higher engagement, focus, and confidence during learning activities. The implementation of PBL successfully created an interactive and enjoyable learning environment that positively influenced motivation and achievement. The study concludes that integrating the PBL model into physical education effectively enhances football shooting skills and fosters active learning behavior among junior high school students.